Building the Older Adult Fall Prevention Movement – Steps and Lessons Learned - Schneider, Ellen C.; Beattie, Bonita Lynn (Frontiers in Public Health, 2015)
Background Falls are the leading cause of older adult injuries and injury-related deaths. Until 2004, the growing public health issue of older adult falls received little national attention. To elevate and focus on the issue, the National Council on Aging launched the Falls Free® Initiative, a group of national and state agencies working collaboratively to address older adult falls with evidence-based solutions. Since then, attention to older adult falls has gained significant momentum. Purpose To describe the steps taken to create the momentum around fall prevention and lessons learned that could be applied to supporting other older adult health-related issues. Method/objectives The Falls Free® Initiative took key steps to promote the older adult falls prevention movement, including initiating organized advocacy and supporting the development of state coalitions through increasing awareness of the issue, promoting evidence-based programs, instituting evaluation, implementing systems change, and providing tailored technical assistance. Results Through the support of the Falls Free® Initiative and many partners, advocacy efforts have increased federal funding for fall prevention, the majority of states have fall prevention coalitions, and thousands of stakeholders are now engaged in fall prevention. Select lessons learned include leveraging compelling data, choosing passionate leaders for the movement, aligning the cause with partner missions, and being inclusive of all stakeholders. Conclusion Although much progress has been made in the fall prevention movement, the issue is growing along with the aging population. Efforts must continue to gain support from all affected stakeholders to reduce older adult falls and fall-related injuries.